2019
DOI: 10.13189/ujer.2019.070303
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevalence and Physical Fitness in School-aged Children

Abstract: The purpose of this study is to determine the overweight and obesity prevalence among students studying in primary school by ages and to reveal the relation with physical activity. 1946 students aged between 7 and 11 and receiving primary education in a district of Manisa province have participated in this study. There are 885 female students and 1061 male students. Height measurements, body composition measurements, vertical jump test and 30mt tests of the participants were performed respectively. SPSS 22 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…We found that the introduction of Kangoo Jumps fitness programs in the educational process of physical education arouse the female students' interest and motivation for exercise, resulting in their increased motor activities. The results of our research confirm the findings of many scientists [39,40,41,42,43,44,45] and expand them.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the introduction of Kangoo Jumps fitness programs in the educational process of physical education arouse the female students' interest and motivation for exercise, resulting in their increased motor activities. The results of our research confirm the findings of many scientists [39,40,41,42,43,44,45] and expand them.…”
Section: Discussionsupporting
confidence: 90%
“…Nowadays one of the important tasks in Ukraine is the concern for the health of the younger generation, which would be ready for dynamic creative activity in all spheres of life of a democratic society [1][2][3][4]. That is why there is a need for highly-qualified specialists in physical culture who would be prepared for the professional activity in modern living conditions because large mental loads of pupils at school, sedentary lifestyle (free time is spent with the computer, tablet, smartphone), bad ecology and inappropriate nutrition lead to health deterioration [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that it is at a young school age the basic physical qualities of a person are formed, children have a rather high need for movements, on the basis of which it is possible to activate pupils for further intellectual and physical development [7][8][9][10]. Taking into account the psychological characteristics of younger pupils, the basic physical education curriculum allows to plan comprehensive classes that will give the possibility to include a variety of physical exercises in the lesson, which will increase the interest and emotional state of pupils [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%